Exploring Students' Perceptions of 'Speakia' App for Speaking Lessons - Irmayani Irmayani; Annis Rahmawati; Syifa Khuriyatuz Zahro (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
This study aims to explore students’ perceptions of